2019
DOI: 10.1177/0306624x19895973
|View full text |Cite
|
Sign up to set email alerts
|

Arab Threat and Social Control: An Exploration of the Relationship Between Ethnic Attitudes and Punitiveness Among Israeli Jews

Abstract: Numerous studies in the United States, as well as a smaller number of studies in other Westernized countries, have linked racial and ethnic attitudes to support for more punitive forms of crime control. The current study explores this relationship in Israel by assessing whether the degree to which Israeli Jews typify crime as an Israeli Arab phenomenon and/or resent Israeli Arabs is related to support for punitive criminal justice policies. The findings suggest that ethnic typification and resentment are relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…Instead of naming a specific minority, our questions referred to people with ‘different ethnic backgrounds'. This is consistent with findings that racial animus directed toward new immigrants (regardless of their skin colour) is associated with an increase in punitive attitudes (Brookman & Wiener, 2017b; Metcalfe & Cann, 2020; Pickett et al, 2015; Welch et al, 2011). To ensure the MRS applied to both the U.S. and Australian sample groups, references to specific countries were replaced with the phrase “in this country.” An example of a modified MRS item is “People of other different ethnic backgrounds should not push themselves where they are not wanted” (see Appendix A for scale items).…”
Section: Methodssupporting
confidence: 91%
“…Instead of naming a specific minority, our questions referred to people with ‘different ethnic backgrounds'. This is consistent with findings that racial animus directed toward new immigrants (regardless of their skin colour) is associated with an increase in punitive attitudes (Brookman & Wiener, 2017b; Metcalfe & Cann, 2020; Pickett et al, 2015; Welch et al, 2011). To ensure the MRS applied to both the U.S. and Australian sample groups, references to specific countries were replaced with the phrase “in this country.” An example of a modified MRS item is “People of other different ethnic backgrounds should not push themselves where they are not wanted” (see Appendix A for scale items).…”
Section: Methodssupporting
confidence: 91%
“…For example, white respondents perceived African‐American and Hispanic individuals as more prone to violence than in‐group members (Pickett, 2016; Unnever & Cullen, 2012). Similarly, Israeli‐Arab individuals are more likely to be identified as criminals and have more serious crimes attributed to them by Israeli‐Jewish respondents (Fishman, Rattner, & Weimann, 1987; Metcalfe & Cann, 2020).…”
Section: Intergroup Bias and Evidence Judgementmentioning
confidence: 99%
“…Recent research has shown that intergroup conflict resulting from historical tensions can increase motivation to protect social identity and in‐group reputation (Branscombe, Warner, Klar, & Fernández, 2015; Tarrant, Branscombe, Warner, & Weston, 2012). The Israeli‐Jewish and Israeli‐Arab ethnic groups can shed light on this phenomenon, as the long‐standing tension between them appears to influence law enforcement policy and sentencing decisions (Grossman, Gazal‐Ayal, Pimentel, & Weinstein, 2016), and contribute to threat, hostility, and negative stereotypes (Canetti, Elad‐Strenger, Lavi, Guy, & Bar‐Tal, 2017; Canetti‐Nisim, Ariely, & Halperin, 2008; Metcalfe & Cann, 2020; Rozmann & Walsh, 2018).…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation